2020
DOI: 10.3390/e22010117
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reaction Networks Possess Intrinsic, Temperature-Dependent Functionality

Abstract: Temperature influences the life of many organisms in various ways. A great number of organisms live under conditions where their ability to adapt to changes in temperature can be vital and largely determines their fitness. Understanding the mechanisms and principles underlying this ability to adapt can be of great advantage, for example, to improve growth conditions for crops and increase their yield. In times of imminent, increasing climate change, this becomes even more important in order to find strategies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The band at 2923 cm −1 was due to C-H stretching from CH 3 and CH 2 functional group for carvacrol, which is the active constituent of dillapiole. The phenolic ring bands at wavenumber 1673-1461 cm −1 and for carvacrol bands at 1194 to 1413 cm −1 were due to C-O stretching of glycerol in biodiesel waste and at 3287.52 cm −1 [31]; [32]. The spectra of the tablet confirmed the incorporation of same bands with no change in position of the functional groups of the marker constituents, but the intensity of band reduced due to product formation (Fig.…”
Section: Atr-ftir Analysis Of Citronella Oil Dillapiole Biodiesel Wmentioning
confidence: 80%
“…The band at 2923 cm −1 was due to C-H stretching from CH 3 and CH 2 functional group for carvacrol, which is the active constituent of dillapiole. The phenolic ring bands at wavenumber 1673-1461 cm −1 and for carvacrol bands at 1194 to 1413 cm −1 were due to C-O stretching of glycerol in biodiesel waste and at 3287.52 cm −1 [31]; [32]. The spectra of the tablet confirmed the incorporation of same bands with no change in position of the functional groups of the marker constituents, but the intensity of band reduced due to product formation (Fig.…”
Section: Atr-ftir Analysis Of Citronella Oil Dillapiole Biodiesel Wmentioning
confidence: 80%
“…44 Dillapiole's synergistic activity is due to the presence of a methoxy group on the aromatic ring. 45 Several studies have revealed that dillapiole is synergistic in combination with synthetic pyrethroids, carbamates, and botanical pesticides. 46−50 In the present study, dillapiole oil's synergistic or combinatory activities were used to enhance the citronella's insecticidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…through the architecture of the reaction network and the physical properties of its components (Rouff et al 2007). Besides having a compensatory nature, the reaction network can offer potential for regulation (Adler et al 2020). Taken together, these processes form a complex system of intertwined mechanisms that is difficult to entangle.…”
Section: Introductionmentioning
confidence: 99%